The applicability of self-determination theory to health coaching: a qualitative analysis of patient experiences. Issue 2 (2nd July 2020) - Denneson, Lauren M.; Ono, Sarah S.; Trevino, Amira Y.; Kenyon, Emily; Dobscha, Steven K.
ABSTRACT: To examine the fit between core concepts of self-determination theory and patient experiences with health coaching, 18 participants at one large United States Veterans Affairs medical centre completed semi-structured, audio-recorded interviews (40–60 min) about their experiences with health coaching. Transcripts were analysed using thematic analysis, and self-determination theory concepts (autonomy, competence, relatedness, and self-integration) were applied to the data. Participant descriptions of their experiences with health coaching were consistent with the process of motivation and goal attainment proposed by self-determination theory. Participants felt the programme supported their sense of autonomy by helping them select goals that were important to them and recognising their ownership over outcomes. Competence was described as the 'confidence' to tackle any challenge and relatedness was discussed as a consistently strong rapport with the health coach. Participants spoke to self-integration by discussing their ability to maintain behaviour change beyond the coaching programme, with some explicitly making the connection between behaviours and their values and life purpose. This study provides initial support for the use of self-determination theory as a theoretical basis of health coaching. Support for patient autonomy, competence, and relatedness may be important components of health coaching practice.